DSP1 and DSP4 Act Synergistically in Small Nuclear RNA 3′ End Maturation and Pollen Growth. Issue 4 (21st June 2019) - Pu, Xuepiao; Meng, Chunmei; Wang, Weili; Yang, Siyu; Chen, Yuan; Xie, Qingjun; Yu, Bin; Liu, Yunfeng
Abstract : DSP1 and DSP4 function synergistically in pollen development and promote pre-snRNA transcription and 3′-end processing efficiency and accuracy. Abstract: Small nuclear RNAs (snRNAs) play essential roles in spliceosome assembly and splicing. Most snRNAs are transcribed by the DNA-dependent RNA polymerase II (Pol II) and require 3′-end endonucleolytic cleavage. We have previously shown that the Arabidopsis ( Arabidopsis thaliana ) Defective in snRNA Processing 1 (DSP1) complex, composed of at least five subunits, is responsible for snRNA 3′ maturation and is essential for plant development. Yet it remains unclear how DSP1 complex subunits act together to process snRNAs. Here, we show that DSP4, a member of the metallo-β-lactamase family, physically interacts with DSP1 through its β-Casp domain. Null dsp4-1 mutants have pleiotropic developmental defects, including impaired pollen development and reduced pre-snRNA transcription and 3′ maturation, resembling the phenotype of the dsp1-1 mutant. Interestingly, dsp1-1 dsp4-1 double mutants exhibit complete male sterility and reduced pre-snRNA transcription and 3′-end maturation, unlike dsp1-1 or dsp4-1 . In addition, Pol II occupancy at snRNA loci is lower in dsp1-1 dsp4-1 than in either single mutant. We also detected miscleaved pre-snRNAs in dsp1-1 dsp4-1, but not in dsp1-1 or dsp4-1 . Taken together, these data reveal that DSP1 and DSP4 function is essential for pollen development, and that the two cooperatively promote pre-snRNA transcription and 3′-end processing efficiency and accuracy.